Peningkatan Produktivitas Petani Jamur Tiram Dengan Press Baglog - Nur, Nila; Nurmala Dyah Fajarningrum; R Faiz Listyanda (LPPM UMRI, 2024)
The Angger Farmer Group in Magelang, Central Java, specializes in oyster mushroom cultivation, boasting strengths like four mushroom production locations, easily accessible growing media, and the ability to cultivate mushrooms in mountainous areas. Despite this, a decline in mushroom production is observed due to a shortage of manpower for baglog production. The group derives income not just from mushrooms but also from the 8-hour process of producing 100 baglogs. Precision is crucial in the baglog pressing process, where inconsistent pressure can lead to plastic breakage, necessitating redoing tasks and increasing production costs. To address these challenges and enhance economic self-sufficiency, the outreach aims to disseminate baglog pressing machines, improving farmer group productivity and fostering economic independence. Management-wise, machine operation training sessions was be conducted. The initiative's outcomes include the dissemination of baglog pressing technology and improved farmer skills in utilizing the technology, resulting in increased baglog production.